Circuits of Labour: A Labour Theory of the iPhone Era - Jack Linchuan Qiu; Melissa Gregg; Kate Crawford (tripleC: Communication, Capitalism & Critique)
This paper questions the binary of material and immaterial labour in the information era. Instead, we propose a “circuits of labour” model, a holistic framework that helps connect various concepts and traditions in the study of labour and ICT (information and communication technology). Inspired by du Gay et al’s “circuit of culture”, we argue conventional frameworks need to be synthesized and updated to reflect fundamental changes and persisting issues of labor in our contemporary era, of which the iPhone is emblematic. On the one hand, our model consists of formal circuits, in which hierarchical domination is imposed by capital over the body of labour. On the other hand, it consists of informal circuits where relationships are defined communally between embodied practices and social and communicative capital. The informal and formal circuits of labour are “short-circuited” by survival labour and ‘playbour’, meaning either circuit may absorb productive energy from the other. This article then uses the case of Foxconn, the world’s largest electronic manufacturer that also produces iPhones, to illustrate the usefulness of the “circuits of labour” model. We finally discuss the broader implications and questions for future research.